MODEL PENDIDIKAN HOLISTIK INTEGRATIF MELALUI SOCIAL EMOTIONAL LEARNING ISLAMI PADA SISWA SEKOLAH DASAR - Muhammad Alfi Syahrin; Rani Asmara; Rifqi Khoiril Anam; Dody Tisna Amijaya (LPPM STAI Muhammadiyah Probolinggo, 2024)
This study aims to analyze the implementation of a holistic-integrative education model through Islamic Social Emotional Learning (ISEL) among elementary school students in Islamic schools. The study employed a qualitative approach using a multiple-case study design conducted at MI Muhammadiyah 1 Probolinggo and SD Muhammadiyah Plus Probolinggo, Indonesia. Data were collected through in-depth interviews, participatory observations, and document analysis involving 20 participants consisting of principals, teachers, students, and parents. Data were analyzed using thematic analysis through the stages of open coding, axial coding, and selective coding. The findings reveal that the implementation of holistic-integrative education was carried out through the integration of spiritual habituation, emotional reflection, social activities, Islamic conflict resolution, and the internalization of Islamic moral values in daily school life. The Islamic Social Emotional Learning model identified in this study consists of five main dimensions: self-awareness, self-management, social awareness, relationship skills, and responsible decision-making, which are integrated with Islamic values such as rahmah (compassion), hikmah (wisdom), ukhuwah (brotherhood), sabr (patience), amanah (trustworthiness), and afwun (forgiveness). The study also found that teachers play a central role as emotional-spiritual mentors who model emotional and spiritual character development for students. Theoretically, this study contributes to the advancement of contemporary Islamic education by extending the concept of Social Emotional Learning through a spiritual-transcendental dimension. Practically, the ISEL model may serve as an alternative paradigm for character education in Islamic elementary schools in addressing the challenges of 21st-century and digital-era education.